PLACE ATTACHMENT STUDY IN KUTA BEACH COMMERCIAL CORRIDOR - Putra, Ida Bagus Gede Parama (Journal of Architectural Research and Education, 2021)
Kuta Beach has undergone a change in function and a shift in activity which began with the opening of the trading port function to become a popular beach tourism area in Bali. The development of tourism on Kuta beach is currently experiencing a very drastic increase as evidenced by the very rapid development of tourist accommodation and infrastructure arrangement by the government. The increase in the number of hotels, inns and various other types of functions indicates the high interest in investment in the Kuta beach road area. Indirectly, this dynamic changes one's bond in the Kuta Beach corridor. The study of Place attachment in the commercial corridor area of Kuta Beach aims to determine the important factors in the formation of a place's identity, corridor characteristics, visitor preferences, activity studies, and magnetic identification of an area. The research method in place attachment studies in the Kuta beach corridor uses a quantitative approach accompanied by a qualitative descriptive explanation to find out the phenomena and perceptions of visitors. Knowing the important variables and elements in the corridor becomes the focus of the study to obtain data on the level of place attachment that exists in the commercial corridor of Kuta beach. Based on the literature study, the place attachment study is one of the cornerstones in assisting the planning of an area by assessing the level of attachment to a place.